Variogram analysis of stochastic processes - Tatsiana V. Tsekhavaya (Журнал Белорусского государственного университета: Математика, информатика, 2018)
Properties of the semivariogram of an intrinsically stationary continuous-time random process with finite second moment are investigated. A necessary and sufficient conditions for a continuous function to be semivariogram are found. Confidence intervals for the semivariogram of Gaussian stationary stochastic process are defined. Properties of ꭓ2-distribution are used for constructing confidence intervals for semivariogram. The proposed confidence intervals are more informative compared with point estimates of the semivariogram.